Effect of Low Carbonization Temperature on Graphitic Properties of Palm Kernel Shell-Derived Carbon - Nurul Aishah Mohd Amran; Muhammad Mahyiddin Ramli; Norizah Abd Karim; Ismariza Ismail; Shazlina Johari; Anis Syafiqa Rosman; Nurul Huda Osman; Darminto; Ali H. Reshak, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
This study explores the impact of carbonization temperature on the structural and defect properties of graphite prepared by means of palm kernel shell (PKS). Carbonization of the samples was carried out at 400, 500, and 600 °C with varying heating rates, and X-ray diffraction (XRD) and Raman spectroscopy were used. XRD analysis of the collected results showed the presence of broad (002) peaks in the range of 22–24°, suggesting the formation of incipient graphitic structures and decreased interlayer spacing with increasing temperature. The sharpest and highest-intensity (002) peak was found in the 600 °C sample carbonizing at 5 °C/min, indicating improved structural stability and ordering of carbon. With respect to the temperature increase, Raman microscopy revealed turbostratic ordering in graphite. Overall, these results demonstrate that low-temperature carbonization promotes incipient graphitic ordering in palm kernel shell (PKS). This approach provides a more sustainable and energy-efficient pathway for producing functional carbon materials, with potential applications in adsorption, catalysis, and energy storage.